(untitled) (Hematology Meeting Reports, 2009)
T-cell non-Hodgkin’s lymphomas (NHL) are rare in Europe and the United States, where they constitute about 10-15% of aggressive lymphomas. The prognostic significance of the immunophenotype has been explored in several studies and results have been reported concerning the outcome of PTCL compared to that of B-cell lymphomas (BCL). PTCL patients were found to have generally poorer prognoses than patients with BCL. However, PTCL represent a heterogeneous group of lymphomas and a wide variety of different histological subtypes have been recognized. The most common subtype is an heterogeneous group of PTCL not other specified (PTCL-NOS), followed by anaplastic large cell lymphoma (ALCL), angioimmunoblastic Tcell lymphoma (AITL). Some uncommon PTCL subtypes have been included in series and are not always easy to identify in reports.